Pemberdayaan Keluarga dalam Pengasuhan Anak dengan Parenting Education dan Optimalisasi Peran Guru dalam Deteksi Dini Perkembangan Anak di TK Aisyiyah Sukodono Sidoarjo - Widowati, Hesty; Hanum, Sri Mukhodim Faridah; Fahmawati, Zaki Nur; Anggraini, Sekarlita Normaulida (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The Covid-19 pandemic has changed all activities in all fields, including the field of education. Early childhood education plays an important role in the mental and character formation of children. Parents must always update their knowledge to be able to educate and care for children according to age and development of the times. During the pandemic, the learning process at Aisyiyah Sukodono Kindergarten was mostly done online, this made it difficult for parents to accompany their children to study at home, besides that teachers had never received training on early detection of child development. This activity aims to optimize the skills of parents in caring for children according to age stages and empower teachers to be able to detect early development of their students. The Service Method is by providing counseling to the guardians of Aisyiyah Sukodono Sidoarjo Kindergarten students about positive parenting to optimize children's potential and providing training on early detection of child growth and development with a developmental pre-screening questionnaire (KPSP) for Aisyiyah Sukodono Sidoarjo Kindergarten teachers. This community service activity was attended by 23 parents and 8 teachers. Based on the results of the assessment before participating in parenting education activities, most of the parents (71%) had less knowledge about parenting, and after participating in the activity, most of the parents (54%) had good knowledge about parenting. Meanwhile, for teachers, before training all of them could not use KPSP and after training, all of them became able to use KPSP for early detection of developments. This shows that there is an increase in the knowledge of parents about child care and teachers are able to carry out early detection of developments with KPSP.